2005
DOI: 10.1159/000083290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micronised Purified Flavonoid Fraction on Pain, Spermiogram and Scrotal Color Doppler Parameters in Patients with Painful Varicocele

Abstract: Purpose: Micronised purified flavonoid fraction (MPFF) is a phlebotropic drug improving venous tone, elasticity and lymphatic drainage, decreasing venous distensibility, venous emptying times, reflux time of venous blood and capillary hyperpermeability, and having antioxidant activities. Since varicocele is a venous pathology, we evaluated the effects of MPFF on pain, spermiogram and color Doppler parameters in patients with painful varicocele. Material and Methods: Semen analyses and Doppler sonography were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Another derivative of bioflavanoid in the form of micronized purified flavonoid fraction (MPFF, commonly available as Daflon) was also evaluated to study its effect on pain score, spermiogram, and color Doppler parameters in patients with clinical painful varicocele after treatment for 6 months. 15 It was found that medical therapy resulted in significant relief of varicocele-associated pain ( P < 0.001), improvement in color Doppler parameters (i.e., decrease in the reflux time of left spermatic vein during Valsalva maneuver; P = 0.003), and improvement in sperm motility ( P = 0.009). It did not lead to any improvement in total sperm count, sperm concentration, morphology, and semen volume.…”
Section: Resultsmentioning
confidence: 96%
“…Another derivative of bioflavanoid in the form of micronized purified flavonoid fraction (MPFF, commonly available as Daflon) was also evaluated to study its effect on pain score, spermiogram, and color Doppler parameters in patients with clinical painful varicocele after treatment for 6 months. 15 It was found that medical therapy resulted in significant relief of varicocele-associated pain ( P < 0.001), improvement in color Doppler parameters (i.e., decrease in the reflux time of left spermatic vein during Valsalva maneuver; P = 0.003), and improvement in sperm motility ( P = 0.009). It did not lead to any improvement in total sperm count, sperm concentration, morphology, and semen volume.…”
Section: Resultsmentioning
confidence: 96%
“…MPFF or Daflon, a derivative of bioflavonoid, has also been studied by Kilic et al . 62 and Soylemez et al . 63 It is thought that these agents prolong the activity of peripheral norepinephrine and ultimately improving venous tone in varicoceles.…”
Section: Multivitaminsmentioning
confidence: 93%
“…Micronised purified flavonoid fraction (MPFF) is an oral phlebotrophic drug that improves the venous tone and elasticity and reduces distension of the veins as well as venous emptying time in patients with chronic venous insufficiency. Kiliç et al [18] that 6 months oral MPFF therapy was safe and effective in a study including 16 patients with painful varicocele. However, no recommendation for the use of MPFF can be made until these preliminary results are confirmed by a randomized, placebo-controlled trial.…”
Section: Treatmentsmentioning
confidence: 99%